(untitled) (Annual of the Faculty of Philosophy in Skopje, 2011)
This article discusses the conceptual and formal fundamentals of relevant logic, which represents one of the most important, but also the most controversial research platforms in contemporary formal logic. The main goal of the adherents of relevant perspective in logic is to build a logical concept of implication which will adequately mirror our intuitive conception of the nature of logical consequence, based on the idea of relevance of the premisses for the conclusion in a valid argument. In the article, the author elaborates the "strong" and the "weak" points of this methodological strategy, especially concerning the inten- sional interpretation of the basic logical operators suggested in its framework.